Evaluasi Tingkat Kebisingan dan Rekomendasi Teknologi Pengendalian Bising di PT X - Serlina, Yega; Evitayani; Yaura Jihan Shabirah; Miftahul Salami (Jurnal Serambi Engineering, 2025)
Noise problems have the potential to occur in PT X which focuses on the provision, processing, and distribution of steel and ready-mix concrete materials. This study was conducted to identify the types and sources of noise, evaluate noise levels, and evaluate the noise control system carried out at PT X. The measurement method used refers to SNI 7231: 2009 concerning the Method of Measuring Noise Intensity in the Workplace and SNI 8427: 2017 concerning Measurement of Environmental Noise Levels. The results of measurements carried out at 4 measurement points showed noise levels in the production area of 86.43 dB (A), and 84.94 dB (A), in the tower area of 79.77 dB (A) and in the concrete area of 95.27 dB (A). Evaluation of the Regulation of the Minister of Manpower of the Republic of Indonesia No. 5 of 2018 showed that noise at points 1 and 4 exceeded the threshold value. PT X carries out technical noise control in the form of engineering control and environmental engineering; administrative control in the form of division of working hours, work rotation, health checks and installation of safety signs; and the use of PPE in the form of earplugs. However, there are still noise control efforts that need to be optimized in their implementation at PT X, namely tightening the rules for the use of PPE and increasing noise absorption areas such as by adding tree planting areas that have the ability to reduce noise.